1985
DOI: 10.1093/cvr/19.11.686
|View full text |Cite
|
Sign up to set email alerts
|

Infarct size limitation by the xanthine oxidase inhibitor, allopurinol, in closed-chest dogs with small infarcts

Abstract: The present study was designed to evaluate the ability of allopurinol to limit infarct size following permanent coronary occlusion in the greyhound. Coronary occlusion was produced by injecting 2.5 mm plastic beads into the coronary artery of the closed chest dog. Non-perfused myocardium, the area at risk, was visualised by autoradiography of 141Cerium labelled microspheres which were infused immediately following coronary embolization. The treated dogs (n = 12) received 400 mg of allopurinol orally one day be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 1 publication
(1 reference statement)
5
30
0
Order By: Relevance
“…This computational result is quite consistent with the proposition of Downey and coworkers 53 that reperfusion injury of heart muscle can occur "without reperfusion" in small myocardial infarcts. According to this concept, even though a coronary artery occlusion is never reopened, oxygen radical injury may develop in the border zones supplied by oxygen diffusion and "trickle" blood flow from adjacent normal muscle.…”
Section: Discussionsupporting
confidence: 91%
“…This computational result is quite consistent with the proposition of Downey and coworkers 53 that reperfusion injury of heart muscle can occur "without reperfusion" in small myocardial infarcts. According to this concept, even though a coronary artery occlusion is never reopened, oxygen radical injury may develop in the border zones supplied by oxygen diffusion and "trickle" blood flow from adjacent normal muscle.…”
Section: Discussionsupporting
confidence: 91%
“…However, they do not preclude the possibility that the inhibition of xanthine oxidase is the primary mechanism by which allopurinol provides protection to the ischaemic myocardium. Despite the recent negative observations of Reimer & Jennings (1985), those findings which implicate xanthine oxidase in the formation of freeradicals in post-ischaemic reperfusion in the myocardium (Gardner et al, 1983;Chambers et al, 1984;Akizuki et al, 1985;McCord, 1985) remain extremely relevant to the myocardial response to haemorrhagic shock and reperfusion. Additional indirect support for this thesis can be found in the protective effects of other free-radical scavenging treatments in the postischaemic, reperfused myocardium (Shlafer et al, 1982;Jolly et al, 1984).…”
Section: Discussionmentioning
confidence: 98%
“…However, there is some evidence that pretreatment with allopurinol increases the survival time (Crowell et al, 1969;Salles et al, 1972). More recently, allopurinol has been found to prevent the damage and loss of function, associated with post-ischaemic reperfusion in a number of different tissues, including the myocardium (Chambers et al, 1984;Akizuki et al, 1985). Hence the protective effects of allopurinol in haemorrhagic shock and reperfusion, specifically in the myocardium, may have more relevance to the events associated with the reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs treated with allopurinol for 48 hours before coronary artery occlusion have exhibited decreased myocardial stunning after regional ischemia for 15 minutes followed by reperfusion. 23 The beneficial effects of allopurinol have been attributed to alleviation of tissue injury during reperfusion, but further studies have found that pretreatment with allopurinol 24 hours before the onset of ischemia limited the extent of myocardial injury in dogs subjected to coronary artery occlusion for 24 hours without reperfusion. 24 The cardioprotective effects of allopurinol appear to depend on a period of long-term pretreatment 21 The results of other recent studies, however, indicate that short-term therapy with allopurinol may be sufficient to inhibit xanthine oxidase.…”
Section: Histological Examinationmentioning
confidence: 99%